Marangoni flow of thin liquid film underneath a topographical plate. (July 2022) - Song, Fenhong; Liu, Yankui; Zhang, Tingting; Fan, Jing; Yang, Qingzhen
Abstract: Marangoni flow occurs when a fluid-fluid free surface is exposed to a non-uniform thermal field. Recently, Marangoni flow has been used to fabricate micro/nano-structures in thin films, which is referred to as thermocapillary patterning. A thin liquid-air film is confined between a hot plate and a topographic cold plate. Marangoni flow thus takes place, and the film evolves into micro/nano-structures that comply with the geometry of the template. In this paper, a numerical model based on the moving mesh method is proposed to study the dynamic process of thermocapillary patterning. Liquid and air are calculated simultaneously with proper boundary conditions imposed at the interface. The numerical model enables characterization of the thermal field and the fluid flow, and thus the deformation of the liquid film. The effect of some key parameters, including temperature difference, template geometry, and liquid film viscosity, on thermocapillary patterning is investigated. The numerical model and the obtained results serve as a useful and representative guide for practical experiments.